Exposure to job-related violence among young female sex workers in urban slums of Southwest Nigeria - Olutoyin Opeyemi Ikuteyijo; Akanni Ibukun Akinyemi; Sonja Merten (BMC, 2022)
Abstract Background In Nigeria, many young girls are engaged in commercial sex work as a means of livelihood and support of dependent relatives. Although studies have documented some of the violence related issues among commercial sex workers, the plight of adolescent and young sex workers particularly in urban slums may be different in context and depth. Objective This study explored the lived experiences of violence and health related harm among vulnerable young female sex workers in urban slums in Ibadan and Lagos, Southwest Nigeria. It also analyzed their coping strategies and survival mechanisms. Design The study is cross-sectional and applied an interpretive phenomenological approach to this qualitative study through in-depth interviews. Participants Young female sex workers ages (15-24 years) who reported having experienced violence were recruited for the study. Twelve participants completed the interviews out the 20 initially contacted. Data collection and analysis Primary data were collected using in-depth interviews (IDIs). Data were transcribed using a phenomenological framework analysis. Participants' reports based on life experiences were identified: lived experience "daily brothel life experience"; sources of violence such as law enforcement agents' intermittent raids; violence experience with clients who often demanded sexual acts beyond the agreed scope; and coping strategies employed to mitigate the challenges. Settings The study was conducted in brothels of two selected slum areas in Ibadan and Lagos, Southwest Nigeria. Results The results showed that the major motivation for engaging in commercial sex work was for economic reasons. However, there are inherent risks involved particularly for the vulnerable young people. Stigmatization from the community, clients' uncontrolled-aggressive behavior and harassment from law enforcement agents are some of the frequent violence experiences reported. Self-help coping strategies are usually employed to prevent or mitigate the challenges. Conclusion The plight of this young people required policy and program attention towards alternative economic empowerment to rehabilitate those willing to leave the profession. Also the need to develop arm reduction interventions towards protection of young sex workers against violence.